Genome-wide analysis of the XTH gene family and functional analysis of DlXTH23.5/25 during early longan somatic embryogenesis - Ma, Xiangwei; Chen, Yan; Liu, Mengyu; Xue, Xiaodong; Zhang, Xueying; Xu, Luzhen; Lai, Zhongxiong; Lin, Yuling (Frontiers in Plant Science, 2022)
Xyloglucan endotransglucosylase/hydrolase (XTH) is a cell wall-modifying protein that affects cell expansion and loosening of the cell wall. This study focused on the regulatory mechanism of DlXTH genes during early somatic embryogenesis (SE) and the heat stress response in longan. Mining of the available D. longan genome sequence yielded 25 putative XTH genes. Transcript profiles based on RNA-seq data showed that most of the 17 detected DlXTH genes were highly expressed in the embryonic callus (EC) (8) and globular embryo (GE) (8), and 13 of them responded significantly to heat stress. ATAC-seq data analysis showed that in terms of chromatin accessibility, 22 of the 25 DlXTH genes were open during early SE, and most of the peak DlXTH genes with transcription differences during early SE were associated with high levels of H3K4me1. The most differentially expressed genes, DlXTH23.5 and DlXTH25, were selected for analysis. According to subcellular localization and quantitative real-time PCR (qRT‒PCR) analysis, DlXTH23.5/25, which encodes cell membrane-localized proteins, were expressed at the highest level in the GE and significantly responded to heat stress. Dual-luciferase assays and transient transformation showed that the transcription factors (TFs) DlWRKY31, DlERF1 and DlERF5 might bound to the DlXTH23.5/25 promoters to activate gene transcription. Transient overexpression of TFs and DlXTH23.5/25 induced XET activity in Nicotiana benthamiana leaves. Under heat stress in the longan EC, the XET activities and expression levels of TFs and DlXTH23.5/25 were significantly increased, and a high concentration of XET might inhibit longan SE. Thus, the regulatory network composed of DlXTH23.5/25 and its related TFs may regulate early longan SE and participate in the regulatory pathway of longan under heat stress via cell wall repair through the action of XET.